Coordinating the day-ahead operation scheduling for demand response and water desalination plants in smart grid - Elsir, Mohamed; Al-Sumaiti, Ameena Saad; El Moursi, Mohamed Shawky; Al-Awami, Ali Taleb (Applied energy, 2023)
Integrating renewable energy resources (RES) is a challenge for power system operators due to their fluctuations and unpredictability. At the same time, the water shortage problem and the needs to desalinate more freshwater increase the prominence of sufficient energy resources for sustainable operation. Therefore, this paper presents a market-clearing mechanism in a co-optimization model that coordinates the operation of grid-connected reverse osmosis water desalination plants (RO-WDPs) and the operation of renewable-rich power systems. It is assumed that electric demands can participate in the provision of demand response (DR) to the market via multiple DR options. The DR options related to the general loads are demand shifting, load curtailment, distributed generation, and hybrid energy storage systems (HESS). These HESS includes battery storage and hydrogen storage systems. Pertaining to their special characteristics, a new DR option is proposed as a customized option for RO-WDPs. The market clearing mechanism is assumed to be based on the security-constrained unit commitment (SCUC) and formulated as a stochastic mixed-integer linear programming problem (MILP) to optimally schedule the day-ahead operation of the power system. The presented model is applied on 6-bus and IEEE 24-bus reliability test system (RTS) test power systems with significant penetration of RES to demonstrate its merits. The simulation results show that the system efficiency is enhanced by adding the energy flexibility of RO-WDP without endangering the water demand-supply when using the proposed coordinated model. Hence, the total operation cost is minimized, the RES integration is facilitated, and the hourly electricity prices are smoothened. •We propose coordination model of grid-connected RO desalination and responsive power system.•The power system in our model considers five DR options including hybrid ESS.•We avoid the generic DR model to reschedule the RO desalination flexibility.•The day-ahead operation of our energy–water nexus incorporates system uncertainties.•The incorporated approach minimizes cost and CO2 and enhances the system flexibility.